YHWH and Israel in the Book of Judges an object-relations analysis - Guest, Deryn (New York Cambridge University Press, 2018)
Reveals Israel's intense relationship with YHWH: a masochistic dance on an epic scale
Cover -- Half-title -- Series information -- Title page -- Copyright information -- Dedication -- Contents -- Acknowledgements -- Introduction -- 1 Problematic Parenting: Donald Winnicott and the YHWH-Israel Relationship -- Introduction -- Five Key Themes in Winnicott's Work -- The Capacity to Be Alone -- The True and False Self -- The Holding Environment -- The Good-Enough Mother -- The Restitutive Gesture -- Applying Winnicott's Thought to the Book of Judges -- Analysis of the Parent/YHWH-Child/Israel Relationship through a Winnicottian Lens -- Israel: The Guilty Innocents -- 'And They Cried Out to YHWH': Israel's Restitutive Gesture -- YHWH's Holding Environment, Israel's Continuity of Being and Capacity to Be Alone -- Conclusion -- 2 Judges' Cyclical Framework and Trauma Theory -- The Promise and Limitations of Trauma Studies -- The Use of Trauma Theory in Biblical Studies -- Trauma Theory as an Interpretative Lens for God-Talk in the Book of Judges -- The Limitations of Trauma Theory as an Interpretive Lens for the God-Talk in Judges -- Humour in Judges -- Literary Artistry in Judges -- Polyphony in the Book of Judges -- Dating Judges: The Impact of Revisionist Theories on Existing Judges Scholarship -- Pre-Eighth Century BCE Material in Judges -- Eighth-Seventh Century BCE Drafts of Judges -- A Sixth Century BCE Draft of Judges -- Fifth-Fourth Centuries BCE Drafts of Judges -- Third Century BCE Drafts of Judges -- Conclusion -- 3 YHWH and Israel in the 'Strange Situation': Attachment Theory and God-Talk -- Introduction -- Attachment Theory: Definitions, Key Theorists and Concepts -- Mary Ainsworth and the 'Strange Situation' -- Key Elements of Attachment Behaviour in the Work of John Bowlby -- Proximity Maintenance -- Effects of Parental Separation -- Antithetical Attachment Behaviour
Subsequent Scholarship on Attachment Categories and Internalised Working Models -- Applying Attachment Theory to the God-Talk in Judg. 2:11-20, 10:6-16 and 1 Sam. 12:7-25 -- Attachment and Abandonment -- Attachment and Affect -- Attachment and Game Play -- Attachment and Abandonment -- Attachment and Affect -- Attachment and Game Play -- Attachment and Abandonment -- Attachment and Affect -- Attachment and Game Play -- Conclusion -- 4 Israel's Masochistic Defence Mechanism -- 'Better to Be a Sinner in a World Ruled by God Than to Live in a World Ruled by the Devil': Fairbairn, Repression, Splitting and Psychic Demons -- Key Aspects of Relational Masochism and Application to the God-Talk in Judges -- Narcissistic Injury -- The Omnipotent Delusion -- Repressed Rage -- Conclusion -- 5 Conclusion: Psychological Theory and Biblical Hermeneutics -- Bibliography -- Index